Financial stress, family relationships, and Australian youths’ transitions from home and school - Cobb-Clark, Deborah; Ribar, David C. (My University, 2012)
We analyze the effect of mothers’ and youths’ reports of family financial stress and relationship dissatisfaction on Australian youths’ transitions into adult roles. We find that mothers’ reports of financial stresses and borrowing constraints are associated with earlier transitions to inactivity, while youths’ reports of financial stresses are associated with earlier nest-leaving. Youths reporting unsatisfactory relationships with parents leave school and move out earlier than their peers, while unsatisfactory relationships between parents are associated with youths making later transitions. Overall, financial stress and dissatisfaction have independent associations with youths’ transitions and youths’ perspectives have different consequences to those of their mothers.
Review of Economics of the Household
Keywords: Families -- Mothers; Stress -- Financial stress; Relationships; Families -- Adolescents and Youth; Adolescents and youth; Families and relationships; Relationships; Families; Stress; Mothers; Financial stress; Adolescents and Youth; Families and relationships; Adolescents and youth